IMPLEMENTATION OF PROBLEM-SOLVING METHODS IN ISLAMIC RELIGIOUS EDUCATION LEARNING - Hendra Susanti; Wahidah Fitriani (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2022)
This study aims to determine problem-solving in Islam and its urgency with PAI learning. This research was conducted because problem-solving is important in all aspects of life, especially in education. Studies on problem-solving have been widely discussed in scientific studies, but researchers wish to present problem-solving from an Islamic point of view by involving the Quran. The research question posed is about how to solve the problem in Islam. and what is the urgency of PAI learning? The research was conducted with a qualitative approach with a literature study research method. Data was collected by examining the content of verses related to problem-solving and various other related literature. The data obtained were analyzed qualitatively and presented descriptively to answer research questions. The results of this study state that in the Qur'an there are various ways that can be done to do problem-solving. Problem-solving is very important in PAI learning by using the methods offered in the Qur'an because PAI learning is integrated with all problems in aspects of life.